2021
DOI: 10.1136/gutjnl-2020-322924
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cancer-associated fibroblast-secreted WNT2 restores dendritic cell-mediated antitumour immunity

Abstract: ObjectiveSolid tumours respond poorly to immune checkpoint inhibitor (ICI) therapies. One major therapeutic obstacle is the immunosuppressive tumour microenvironment (TME). Cancer-associated fibroblasts (CAFs) are a key component of the TME and negatively regulate antitumour T-cell response. Here, we aimed to uncover the mechanism underlying CAFs-mediated tumour immune evasion and to develop novel therapeutic strategies targeting CAFs for enhancing ICI efficacy in oesophageal squamous cell carcinoma (OSCC) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 43 publications
(50 reference statements)
4
67
0
1
Order By: Relevance
“…PC-unique expression of FZD9 supports a WNTreceptive PC role 60 (Fig. S9), with its expected ligand WNT2 61 absent in our database yet induced in intestinal inflammation and cancer [62][63][64] . Mature PCs can dedifferentiate following injury in mice [65][66][67] , and Ascl2 is required for dedifferentiation in mouse crypts 68 .…”
Section: Paneth Cellssupporting
confidence: 65%
“…PC-unique expression of FZD9 supports a WNTreceptive PC role 60 (Fig. S9), with its expected ligand WNT2 61 absent in our database yet induced in intestinal inflammation and cancer [62][63][64] . Mature PCs can dedifferentiate following injury in mice [65][66][67] , and Ascl2 is required for dedifferentiation in mouse crypts 68 .…”
Section: Paneth Cellssupporting
confidence: 65%
“…In line with this, one study in a melanoma model has shown that expansion and activation of TIDCs at the tumor site by recruiting and activating agents such as FLT3L and poly I:C, enhanced therapeutic response to immune checkpoint inhibitors (196). In addition, a recent study indicates that blocking CRCinduced WNT2 secretion by CAFs restores DC functions enhancing anti-PD-1 efficacy (197). These studies emphasize the importance of functional DCs in effective intra-tumoral DC-T cell crosstalk for immunotherapy response.…”
Section: Tumor-induced DC Dysfunction and Immunotherapy Efficacymentioning
confidence: 77%
“…VEGF and hepatocyte growth factor (HGF) can regulate angiogenesis ( 193 , 197 ). Moreover, by cytokine production and surface molecules, CAF can regulate immunity, including macrophage recruitment, T cells immune response, and DCs anti-tumor immunity ( 198 ). LncRNAs can regulate CAF activation, tumor progression, and chemoresistance.…”
Section: Lncrnas Regulate Tumor Immune Microenvironmentmentioning
confidence: 99%